Two new subterranean-adapted pseudoscorpions (Pseudoscorpiones: Neobisiidae: Parobisium) from Beijing, China - Feng, Zegang; Wynne, J. Judson; Zhang, Feng (Zootaxa, 2019)
Two new troglomorphic pseudoscorpion species, Parobisium magangensis sp. n. and P. yuantongi sp. n., belonging to the family Neobisiidae, are described based on specimens collected in karst caves from Beijing, China. These are the first troglomorphic pseudoscorpions discovered from caves in northern China. Detailed diagnosis, descriptions, and illustrations are provided. We also offer future research and management recommendations for these two new pseudoscorpion species.